Rádio e renovação política em eleição majoritária: a vitória eleitoral de prefeito/radialista em Ponta Grossa - Emerson Urizzi Cervi (Mediações: Revista de Ciências Sociais, 2002)
The interest for the study of the effects of the mass communication in the contemporary societies, especially in the electoral processes. it is growing. lt has been common to verification of the existence of an interdependence relationship among the propagation of the political speech through the broadcastings and the phenomenon of the political populism. The present work analyzes the importance of the Radio for the mayor's of a broadcaster/politic election in the city of Ponta Grossa. Through the study of the characteristics of the local political elites, of the effects of the implanted public politics and of the crises of the situation for the which passed the voters of that city. it is possible to identify the origin of the acceptance of the speech neopopulist. Being like this, it can be said that the phenomenon broadcaster/polític is not born in the waves of the radio, but through them it gets to spread the idea of change.